(untitled) (Journal of Geography and Environmental Management, 2019)
The given article considers the issues of terrain objects’ discernment by their qualitative and quarantitative characteristics with conferment of appropriate symbols in accordance with the government instructions concerning the deciphering of large scale aerial photographs and photo plans for the purpose of the land organization necessary for the compilation of the large scale geographic (topographic) maps used in general and applied sciences.